Profitability as a Mediating Variable in the Influence of Debt-to-Equity Ratio, Current Ratio, and Managerial Ownership on Firm Value (Study of Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange) - Suseno, Bambang; Widiyanti, Marlina; Malinda, Shelfi; Andriana, Isni (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The purpose of this study is to examine the effects of Debt to Equity Ratio, Current Ratio, and Managerial Ownership on Firm Value with Return on Assets as a mediating variable. Using purposive sampling, 18 property and real estate companies listed on the Indonesia Stock Exchange during 2019-2023 were analyzed, resulting in 90 data points. This study employs a descriptive quantitative method to analyze the relationships among Debt to Equity Ratio, Current Ratio, Managerial Ownership, Return on Assets, and Firm Value. Data were collected from 18 property and real estate companies listed on the Indonesia Stock Exchange from 2019 to 2023, using a purposive sampling technique, resulting in 90 data points. Path analysis was utilized to determine the direct and indirect effects of the variables, supported by classical assumption tests to ensure the validity and reliability of the model. Hypothesis testing was conducted through t-tests and F-tests, complemented by determination coefficient analysis to evaluate the explanatory power of the variables. The results show that DER negatively affects ROA, KM positively affects FV, and ROA positively affects FV while mediating the effect of DER on FV. This study highlights the importance of managing debt effectively and incentivizing managerial ownership to enhance firm value. The findings of this study provide valuable insights for stakeholders in the property and real estate sector. By demonstrating the mediating role of Return on Assets in the relationship between Debt to Equity Ratio and Firm Value, the research emphasizes the critical need for effective financial management strategies. Additionally, the positive impact of Managerial Ownership on Firm Value highlights the importance of aligning management interests with shareholder goals. These insights can serve as a foundation for policymakers, investors, and company executives to implement practices that optimize financial performance and sustain long-term growth in a competitive market environment.